2006
DOI: 10.1097/01.ccm.0000194540.44020.8e
|View full text |Cite
|
Sign up to set email alerts
|

Acute lung injury in patients with subarachnoid hemorrhage: Incidence, risk factors, and outcome

Abstract: Acute lung injury is common in patients with subarachnoid hemorrhage and is independently associated with a worse clinical outcome. Research is needed to determine the causes of acute lung injury in this population and whether these patients are candidates for evidence-based ventilator strategies to reduce mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
158
3
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(173 citation statements)
references
References 28 publications
7
158
3
5
Order By: Relevance
“…Some reports have demonstrated that a significant part of patients with acute brain injury develop pulmonary complications. 22,23 Three major causes of pulmonary complications are recognized in brain injured patients: neurogenic pulmonary edema, ventilation-perfusion mismatch, and structural parenchymal abnormalities. 24 In animals, severe brain injury can trigger sympathetic activation that increases pulmonary vascular resistance, resulting in pulmonary edema.…”
Section: Respiratory Failure and Biomarkersmentioning
confidence: 99%
“…Some reports have demonstrated that a significant part of patients with acute brain injury develop pulmonary complications. 22,23 Three major causes of pulmonary complications are recognized in brain injured patients: neurogenic pulmonary edema, ventilation-perfusion mismatch, and structural parenchymal abnormalities. 24 In animals, severe brain injury can trigger sympathetic activation that increases pulmonary vascular resistance, resulting in pulmonary edema.…”
Section: Respiratory Failure and Biomarkersmentioning
confidence: 99%
“…In previous reports, ARDS occurs in up to 20-38% of cases of subarachnoid haemorrhage [13][14][15], traumatic brain injury [1,16] and spontaneous intracerebral haemorrhage [4,5,17,18], and 35% reported in a mixed cohort of neurologically ill patients [19]. Variability in ARDS incidence may reflect differences in study populations and in diagnosis approach, variable use of consensus approach.…”
Section: Discussionmentioning
confidence: 99%
“…ARDS was also associated with a significant increase in mortality, and it prolonged the duration of mechanical ventilation and the length of ICU stay. Similarly, in previous reports, ARDS has been identified as a major contributor to the morbidity and mortality of patients with brain injuries [2,3,5,15,17,18,30]. ARDS also worsens longterm neurologic outcome [1,2,3,32], and is associated with longer ICU and hospital length of stay [5,29].…”
Section: Discussionmentioning
confidence: 99%
“…Actualmente las complicaciones médicas no neurológicas siguen provocando morbilidad, mortalidad y aumento de estancias en UCI y hospitalarias y generando costes añadidos [75][76][77] . Junto a la presencia frecuente de fiebre, anemia e hiperglucemia son las complicaciones respiratorias 78 , cardiológicas 79 y los trastornos electrolíticos las alteraciones más frecuen- …”
Section: Complicaciones Sistémicasunclassified